M-PESA mobile money: a case study in Blue ocean strategy - Mbugua, Moore (2015)
The recent and widespread availability of affordable mobile phone technology in developing countries has paved the way for the development of a number of mobile money and electronic remittance services. One of the most successful of these services is Safaricom’s M-PESA program, launched in the East African nation of Kenya in March 2007. Since then, the program has successfully enrolled over 15.2 million users, transferred more than US$1.4 trillion in electronic funds, and contributed significantly to poverty alleviation and financial inclusion efforts in Kenya. M-Pesa is a mobile phone based money transfer system in Kenya which grew at a blistering pace following its inception in 2007. This case study will analyze the critical factors that make M-PESA such a unique success in Kenya specifically.